Optimization of xylanase production by Bacillus circulans D1 in submerged fermentation using response surface methodology - Bocchini, D. A.; Alves-Prado, H. F.; Baida, L. C.; Roberto, I. C.; Gomes, E.; Da Silva, R. (Elsevier B.V., 2002)
In this work, a 3(3) factorial design was performed with the aim of optimizing the culture conditions for xylanase production by an alkalophilic thermophilic strain of Bacillus circulans, using response surface methodology. The variables involved in this study were xylan concentration (X-1), pH (X-2) and cultivation time (X-3). The optimal response region was approached without using paths of steepest ascent. Statistical analysis of results showed that, in the range studied, only pH did not have a significant effect on xylanase production. A second-order model was proposed to represent the enzymic activity as a function of xylan concentration (X-1) and cultivation time (X-3). The optimum xylan concentration and cultivation time were 5 g/l and 48 h, respectively. Under these conditions, the model predicted a xylanase activity of 19.1 U/ml. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: Bacillus circulans; xylanase; experimental design; optimization